Literatura infantil: estratégias sociocognitivas de leitura - Idalgo, Elisa Garcia Bertoni (2014)
This research aims to analyze how the Anglo apostilled System of Education in their curriculum addresses the issue of Children's Literature involving the socio-cognitive strategies based on the studies of Koch (2009 ) , Koch and Elias (2010 ) , Kleiman (2011 ) , Solé ( 1998) and other scholars of linguistics and textual references cited the four handouts Anglo Teaching System . The corpus chosen for this study represents the didactic material apostilled System Anglo Teaching Early Childhood Education - Level II related to the age of five years . The research methodology consists primarily of bibliographical author dealing with strategies and readings by authors who dedicate their research to Children's Literature . After an analysis of how the material covers the socio-cognitive strategies in reading Children's Literature was held . We sought as a hypothesis , observe , from the proposed objective , the Anglo Education System aims , through its apostilled courseware , take the kids to the most relevant reading practices , which are permeated by all disciplines to the curriculum . It was shown that the conquest of the little reader develops through the pleasant relationship with the children's book, in which dream, fantasy and imagination mingle into one reality , and lead to experience emotions in partnership with the characters of the story , thus introducing situations of reality . Keywords: children´s literature; textual linguistics; socio-cognitive strategies; Apostilled Anglo Learning System.